Biocontrol of Geosmin Production by Inoculation of Native Microbiota during the Daqu-Making Process - Hai Du; Junlin Wei; Xitong Zhang; Yan Xu (Fermentation, 2022)
Geosmin produced by Streptomyces can cause an earthy off-flavor at trace levels, seriously deteriorating the quality of Chinese liquor. Geosmin was detected during the Daqu (Chinese liquor fermentation starter)-making process, which is a multi-species fermentation process in an open system. Here, biocontrol, using the native microbiota present in Daqu making, was used to control the geosmin contamination. Six native strains were obtained according to their inhibitory effects on Streptomyces and then were inoculated into the Daqu fermentation. After inoculation, the content of geosmin decreased by 34.40% (from 7.18 ± 0.13 μg/kg to 4.71 ± 0.30 μg/kg) in the early stage and by 55.20% (from 8.86 ± 1.54 μg/kg to 3.97 ± 0.78 μg/kg) in the late stage. High-throughput sequencing combined with an interaction network revealed that the fungal community played an important role in the early stage and the correlation between Pichia and Streptomyces changed from the original indirect promotion to direct inhibition after inoculation. This study provides an effective strategy for controlling geosmin contamination in Daqu via precisely regulating microbial communities, as well as highlights the potential of biocontrol for controlling off-flavor chemicals at trace levels in complex fermentation systems.